Vocal Self-Perception of Home Office Workers During the COVID-19 Pandemic - Siqueira, Larissa Thaís Donalonso (J Voice, 2023)
OBJECTIVE: To investigate the self-perception of vocal fatigue symptoms and musculoskeletal pain in home office workers before and during the coronavirus disease (COVID-19) pandemic. MATERIALS AND METHODS: A total of 424 individuals participated in this cross-sectional, observational, and descriptive study; they were stratified into the experimental group (EG), consisting of 235 individuals working from home office during the COVID-19 pandemic; and the control group (CG), with 189 individuals who continued to work in person during this period. All participants answered the vocal fatigue index and the musculoskeletal pain investigation questionnaires. The data were analyzed in a descriptive and inferential manner. RESULTS: Participants in the EG reported more vocal fatigue symptoms and musculoskeletal pain than those in the CG before the pandemic. However, during the pandemic, the EG presented a higher frequency of pain in the posterior of the neck, shoulder, upper back, and temporal and masseter muscles, while the CG presented a higher frequency of pain in the larynx. With regard to vocal fatigue, during the pandemic, EG had an increase in scores to factors such as tiredness and voice impairment, avoidance of voice use, and total scores. No such differences were noted in the CG. CONCLUSION: Workers who migrated to home offices during the COVID-19 pandemic are at risk of developing vocal disorders.